Architecture drawing for toilet of PT3+PT4(1F) (RFA-542_Rev. B) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.